The role of CDM and JI for fulfilling the European Kyoto commitments - Helen Lückge; Sonja Peterson (Kiel Institute for World Economics (IfW), 2004)
To meet their Kyoto targets under the Burden Sharing Agreement, most European countries plan to make use of the flexible project mechanisms "Clean Development Mechanism" (CDM) and "Joint Implementation" (JI). In addition, CDM and JI credits can be used by installations to fulfil their obligations in the upcoming European emissions trading scheme. This paper compiles information from a variety of sources to give an overview over the different options to acquire CDM and JI credits and the extent to which European governments and companies plan to make use of these options.
Keywords: Q48; Q54; Q58; 330; CDM and JI; Emissions trading; European Union; Joint Implementation; Klimaschutz; EU-Staaten